Corporate Social Responsibility, Political Connections, and Firm Value: The Moderating Role of Corporate Governance toward SDG 16 - Siti Nurlaela; Rahmawati Rahmawati; Ari Kuncara Widagdo; Setyaningtiyas Honggowati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examine the influence of Corporate Social Responsibility (CSR), political connections, and managerial incentives on firm value, with corporate governance serving as a moderating variable. The study also contributes to SDG 16 by exploring how corporate governance and accountability mechanisms influence firm value in the mining sector. Method: Employing a quantitative approach using secondary data obtained from the annual reports of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. A total of 27 companies were selected through purposive sampling, resulting in 135 firm-year observations. Firm value is measured using Tobin’s Q, CSR is assessed using the Global Reporting Initiative (GRI) index, political connections are identified through politically connected board members, and managerial incentives are measured using a natural logarithm formula. The hypotheses were tested using multiple linear regression and Moderated Regression Analysis (MRA). Results: The findings indicate that Corporate Social Responsibility and managerial incentives have a positive and significant effect on firm value. In contrast, political connections do not significantly affect firm value. Furthermore, corporate governance is found to strengthen the relationship between managerial incentives and firm value, indicating its important role in promoting effective managerial decision-making and corporate performance. Novelty: Extending the literature by simultaneously examining CSR, political connections, and managerial incentives in determining firm value while incorporating corporate governance as a moderating variable in the mining sector. The findings provide evidence that effective governance mechanisms can enhance firm value and support transparency, accountability, and institutional quality in line with SDG 16.